Calculation of D-axis and Q-axis Inductances and Characteristics of PM Motor by Global Cross-coupling Method - WANG Yu; FENG Jianghua; LI Weiye; FENG Shouzhi; SHI Junxu; CHEN Zhichu (Kongzhi Yu Xinxi Jishu)
Calculation accuracy of the PM motor’s characteristics depends on the accuracy of the calculation for d-axis and q-axis inductances. In order to research the exact calculation method, a 2D FEM model was built based on an electric vehicle motor. Ld and Lq was calculated based on the d-axis and q-axis flux linkage model, taking global cross-coupling effect into account. Ld and Lq were calculated again by the method of the frozen permeability and the results were in accordance with the ones by cross-coupling method; moreover, the calculated results of key parameters such as the character of torque and speed, efficiency map, etc are nearly identical with the practical test results, which verified the validity of the calculation method.